Genome analysis of drought tolerant rhizobacteria - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1997)
Three different isolates of drought-tolerant rhizobacteria capable of producing an osmolyte, betaine, have been obtained from different rhizospheres of plants. Genomic DNA preparations from the three isolates have been analysed by restriction enzyme digestion followed by both conventional and Pulsed Field Gel Electrophoresis (PFGE). Restriction enzymes digestion pattern revealed that the three isolates had significant differences in terms of restriction sites within the genome. The PFGE results confirmed that the three isolates had different genomic structures, despite the fact that they demonstrated similar response to drought, as evidence by the capability of producing betaine. The results thus suggest that different rhizobacteria) isolates obtained from different habitats, show polymorphisms in terms of DNA sequences related to drought-tolerance properties.